Analisis Kesulitan Siswa Berdasarkan Kemampuan Berpikir Kreatif Matematis dalam Menyelesaikan Soal Bangun Ruang - Nur Aidah; Hikmatul Khusna (Universitas Sultan Ageng Tirtayasa, 2021)
This research aims to describe students' difficulties based on the level of mathematical creative thinking ability in solving polyhedron problems. This study uses a qualitative descriptive approach with data collection methods in the form of tests and interviews. The subjects of this study were 6 students of class VIII SMP Negeri 11 Bekasi. The instrument used is a test of mathematical creative thinking skills and interviews. The data analysis technique is by examining the results of the subject's answers to be categorized into mathematical creative thinking ability levels, then interviews are carried out. The findings show that the students with high creative thinking skills experience operational technical difficulties, students with medium creative thinking skills experience conceptual and procedural difficulties, and students with low creative thinking skills experience all types of difficulties, namely conceptual, procedural and operational techniques difficulties. The most experienced difficulties are operational techniques such as errors in calculations and not being careful when solving polyhedron problems.